Root Canal Morphology of Maxillary First and Second Molars in a Qatari Population: A Cone-Beam Computed Tomography Study - Al-Obaid, Maryam Mohammed; Al-Sheeb, Fatima Abdullah (European Dental Research and Biomaterials Journal, 2021)
Objective The purpose of this study was to evaluate the number of roots and canal configuration of maxillary first and second molars in Qatari population.Materials and Methods A total of 544 cone-beam computed tomography (CBCT) records of Qatari patients were included in this study. The CBCT images were reviewed by two endodontists. The age, sex, bilateral symmetry, root number, and canal configuration according to Vertucci were tabulated.Results About 97.5% maxillary first molars had three roots and 2.5% had two roots. Maxillary second molar showed 88.2% three roots, 7.3% two roots, 3.3% single root, and 1.2% four roots. For maxillary first molars, the most common Vertucci classifications for the mesiobuccal root were type IV (2-2, 35.9%) and type II (2-1, 21.1%). For maxillary second molars, the most common Vertucci classifications for the mesiobuccal root were type IV (2-2, 27%), type III (1-2-1, 21.3%), type I (1, 19.6%), and type II (2-1, 18.9%). In maxillary first molar, 53.1% right is different from the left and in maxillary second molars, 60.2% right is different from the left.Conclusions In Qatari population, three roots are common in maxillary molars. Mesiobuccal root of maxillary first molars is predominant with Vertucci type IV (2-2) and type II (2-1). Maxillary second molars showed variable Vertucci classification. High bilateral asymmetry was found in canal configuration of the same individuals that should be considered during root canal treatment of two opposite molars.
Keywords: Qatari population; maxillary molars; morphology